UPAYA PEMERINTAH DESA DALAM MENSEJAHTERAKAN MASYARAKAT DESA SETELAH BERLAKUNYA UU NO. 06 TAHUN 2014 TENTANG DESA - M, Muksin (Ahkam: Jurnal Hukum Islam, 2020)
The concept of village development has changed since the passing of Law number 06 of 2014. These changes have had a major impact on the concept of village development ranging from broader authority granted to village governments to the authority of village financial management. All these authorities have demands and responsibilities to the village government to strive for the welfare of the village community. The welfare of the village community becomes mandatory after the enactment of Law number 06 of 2014 concerning the Village, implicitly or explicitly giving clear instructions and making guidelines to the village government to maximize all efforts in realizing the welfare of the village community either through physical infrastructure development or human resource development. Because the village is a miniature of the Republic of Indonesia,the benchmark of the success and the progress of Indonesiaare reflectedby the smallest entity in the scale of village government. The impact of development in the village will be directly felt by the village community as a whole and indirectly affect the progress of the Republic of Indonesia.